Producing more food with less water in a changing world: assessment of water productivity in 10 major river basins - Cai X; Molden, David J.; Mainuddin, M.; Sharma, B.; Ahmad, M.D.; Karimi, P. (Informa UK Limited, 2011)
Conventional wisdom says that the world is heading for a major water crisis. By 2050, global population will increase from 7 billion to a staggering 9.5 billion and the demands this will place on food and water systems will inevitably push river basins over the edge. The findings from this book present a different picture. While it is convenient to visualize an inevitable global water and food crisis in which increasing demands result in increasing poverty, food insecurity and conflict, the reality is far more nuanced and revolves around the politics of equitable and sustainable development of resources. The first part of this book provides detailed insight into conditions of water flows within nine river basins. In the second part, authors summarize and re-analyze the outcome of the nine basins, providing a coherent global picture of water, water productivity and development. They assess the impacts of variations of these attributes on development and approaches for poverty alleviation, and explore the institutional factors that support or obstruct change. How people will manage river systems while protecting vital ecosystem functions will make the difference between catastrophe and survival. As Prof Asit Biswas points out, "… the world is facing a water crisis not because of physical scarcity of water but because of poor management practices in nearly all countries of the world." The book is based on the four years (2006-2010) of extensive research into the state of ten of the world’s major river basins carried out under the CGIAR Challenge Program for Water and Food’s Basin Focal Project.